2017
DOI: 10.1002/jbm.a.36054
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐agarose scaffolds supports chondrogenesis of Human Wharton's Jelly mesenchymal stem cells

Abstract: Tissue engineering strategies for cartilage aim to restore the complex biomechanical and biochemical properties of the native cartilage. To mimic the in vivo microenvironment, we developed a novel scaffold based on chitosan-agarose (CHAG scaffold) resembling the properties of native cartilage extracellular matrix (ECM) that aids in vitro cartilage formation. The CHAG scaffolds had pore size ranging from 75 to 300 µm and the degradation of 18% over 6 months in PBS. L929 cells and Human Wharton's Jelly-Mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…However, the scaffold in wet condition decreased their mechanical strength, that did not match the natural tissue. This limitation could be solved in future by introducing a third component as done in other cases in which as example materials as fibroin (Park et al., 2012; Singh et al., 2016) of chitosan (Merlin Rajesh Lal et al., 2017) have been blended with the Agr to improve its mechanical response. The presence of ESM in the scaffold was proved effective in sustaining the cells proliferation during an in vitro test.…”
Section: Discussionmentioning
confidence: 99%
“…However, the scaffold in wet condition decreased their mechanical strength, that did not match the natural tissue. This limitation could be solved in future by introducing a third component as done in other cases in which as example materials as fibroin (Park et al., 2012; Singh et al., 2016) of chitosan (Merlin Rajesh Lal et al., 2017) have been blended with the Agr to improve its mechanical response. The presence of ESM in the scaffold was proved effective in sustaining the cells proliferation during an in vitro test.…”
Section: Discussionmentioning
confidence: 99%
“…Agarose- and alginate-based polymers have been studied for cellular seeding of chondrocytes for tissue engineering purposes [ 98 , 99 , 100 , 101 ]. They are applicable to be mixed either together or with some other polymer material, such as with chitosan to form a composite material to improve mechanical strength, porosity, cellular adhesion, or some other desired feature of scaffolds [ 102 ]. Although many cell types can be encapsulated in agarose- or alginate-based hydrogels and many in vitro studies have revealed a compatibility of carbohydrate hydrogels to maintain chondrogenic or chondrocyte-specific phenotype [ 99 , 101 ], routine therapy-related clinical applications have not been reported.…”
Section: Scaffolds For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…It is noteworthy that both the production method of the bone scaffolds and also their composition are innovative since there are no studies in the literature describing biomaterials made of a chitosan-agarose cryogel matrix reinforced with HA nanopowder. Scientific reports published by other authors present biomaterials for potential bone regenerations which were fabricated by applying completely different production methods and using only two of the mentioned components, e.g., scaffolds composed of only chitosan and hydroxyapatite [11,12], agarose and hydroxyapatite [13,14,15] or chitosan and agarose [16].…”
Section: Introductionmentioning
confidence: 99%